P099 IL-33 activates CD73-expressing cells promoting tumorigenesis during colitis-associated colorectal cancer. (30th January 2023) - Lopetuso, L R; Privitera, G; Di Martino, L; Scaldaferri, F; Gasbarrini, A; Cominelli, F; De Salvo, C; Pizarro, T
Abstract: Background: Colorectal cancer associated to chronic colitis (CAC) has a different pathogenesis compared to sporadic or familial colorectal cancer and represents the major complication of IBD. IL-33 and its receptor, ST2, are important factors in the pathogenesis of IBD. Emerging evidence suggests the potential contribution to inflammation-driven tumorigenesis that can lead to CAC. The aim of our study was to characterize the precise contribution of IL-33/ST2 axis in the azoxymethane (AOM)/dextran sodium sulfate (DSS) model of CAC. Methods: C57/BL6 wild-type (WT), Il33 -/-, T1/ St2 -/- and Nt5e -/- mice were given a single dose of AOM followed by two cycles of 3% DSS for 7d in drinking water. Vehicle-treated WT mice served as controls and were sacrificed at the same time points. Another group of WT followed the same protocol and received CD73 inhibitor i.p. treatment or vehicle. Disease Activity Index, endoscopic, stereomicroscopic and histological evaluations of colons were performed. IHC, immunofluorescence (IF), qPCR, and ELISA were done on full-thickness colons. RNA-Seq was performed on whole tissues from AOM/DSS treated WT, Il33 -/- and T1/ St2 -/- . qPCR analysis was done on isolated polyps from WT, Il33 -/- and T1/St2 -/- for Nt5e (CD73) and adenosine pathway targets. Results: Il33, Ilrl1 (ST2L), and Ilrl1 (sST2) mRNA transcripts, as well as IL-33 and total ST2 proteins were dramatically elevated in AOM/DSS-treated WT mice vs. controls. IHC and IF of treated WT mice revealed localization of IL-33 to the colonic epithelium and to cells within the polyp LP morphologically consistent with stromal and mast cells. Using IF, IL-33 co-localized with sub-epithelial myofibroblast markers Actin and Vimentin, or with mast cell markers Tryptase and MCPT1. AOM/DSS treatment in Il33 -/- and T1/ St2 -/- mice resulted in a significant decreased polyp number and size vs. WT, with colonoscopy revealing the development of protruding lesions with abnormal vascular patterns, suggesting tumorous lesions in WT mice, while all deficient mice showed their absence with a more impressive mucosal inflammation, likely due to reduced epithelial proliferation and repair caused by the deficiency of IL-33 signaling. RNA-Seq identified a significant reduction of Nt5e and adenosine pathway targets in Il33 -/- and T1/ St2 -/- vs. WT. qPCR on isolated polyps confirmed this observation. AOM/DSS-treated Nt5e -/- showed a significant decreased polyp number and size vs. controls. Therapeutic inhibition of CD73 produced similar results. Conclusion: Our results suggest that the IL-33/ST2 axis promotes tumorigenesis in CAC through the activation of CD73. Further studies are underway to determine mechanisms of action that support these findings.